1999
DOI: 10.1128/mcb.19.7.4664
|View full text |Cite
|
Sign up to set email alerts
|

A RAG1 and RAG2 Tetramer Complex Is Active in Cleavage in V(D)J Recombination

Abstract: During V(D)J recombination two proteins, RAG1 and RAG2, assemble as a protein-DNA complex with the appropriate DNA targets containing recombination signal sequences (RSSs). The properties of this complex require a fairly elaborate set of protein-protein and protein-DNA contacts. Here we show that a purified derivative of RAG1, without DNA, exists predominantly as a homodimer. A RAG2 derivative alone has monomer, dimer, and larger forms. The coexpressed RAG1 and RAG2 proteins form a mixed tetramer in solution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
92
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 31 publications
7
92
1
Order By: Relevance
“…Both cleavage steps are minimally supported in vitro in a protein-DNA complex, termed a stable or single complex (SC), containing a RAG-1 dimer and one or two subunits of RAG-2 bound to an isolated RSS (4,46,48). HMG-1 and HMG-2 can be stably incorporated into the SC (30,47,51).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both cleavage steps are minimally supported in vitro in a protein-DNA complex, termed a stable or single complex (SC), containing a RAG-1 dimer and one or two subunits of RAG-2 bound to an isolated RSS (4,46,48). HMG-1 and HMG-2 can be stably incorporated into the SC (30,47,51).…”
mentioning
confidence: 99%
“…In one model of the PC, RAG-1 and RAG-2 are bound as a mixed tetramer containing two molecules of each protein, based on the following lines of evidence: (i) RAG-1 alone forms a stable dimer in solution (4) and retains this configuration when bound to DNA (37), regardless of whether RAG-2 is present (48); (ii) RAG-1 and RAG-2 associate as a tetramer in solution (in a 1:1 ratio) (4); and (iii) two active sites are present in each dimer of RAG-1, one contributed from each RAG-1 subunit (22,46). However, recent studies provide indirect evidence suggesting that the PC contains a larger number of RAG-1 protomers, possibly a tetramer (22,31).…”
mentioning
confidence: 99%
“…It has been shown that the recombination intermediates are held in a postcleavage complex that contains RAG1 and RAG2 proteins (27,28,46). The purified RAG1/2 proteins were found to mediate the reverse reaction of the cleavage to generate hybrid joints and open-shut products (31).…”
Section: Figurementioning
confidence: 99%
“…RAG1 and RAG2 proteins have been shown to possess end-processing activities, including binding of recombination intermediates (27,28), nicking synthetic hairpin ends (29,30), and rejoining cleaved signal ends to coding ends (31). Recently, it has been demonstrated that the Mre11 protein, when complexed with Rad50 and the Nijmegen breakage syndrome gene product, Nbs1, exhibits several nuclease activities in vitro, such as hairpin nicking and processing of opened ends (32).…”
mentioning
confidence: 99%
“…Some experiments indicated the presence of a dimer of RAG1 (18,22,23,24), whereas others argue for the presence of three or four RAG1 subunits (25,26). RAG2 is present in the SC either as a monomer (18) or as a dimer (23,26).…”
mentioning
confidence: 99%